Kaempferol Improves Lung Ischemia-Reperfusion Injury via Antiinflammation and Antioxidative Stress Regulated by SIRT1/HMGB1/NF-κB Axis - Yang, Chunli; Yang, Wenkai; He, Zhaohui; He, Huiwei; Yang, Xiaogang; Lu, Yuanhua; Li, Hongbo (Frontiers in Pharmacology, 2020)
Trauma, organ transplantation and thromboembolism are the main causes of lung ischemia-reperfusion injury (LIRI), and new therapies and drugs are urgent to relieve LIRI. In preliminary experiment, authors found that kaempferol could improve LIRI in rats, and the current study further explored its possible mechanism. The model of rat LIRI was established and appropriate research methods were implemented. Results shown that kaempferol could significantly improve LIRI, inhibit release of inflammatory factors including interleukin (IL) 6 and tumor necrosis factor (TNF) α in bronchoalveolar lavage fluid, and reduce oxidative stress reaction. Western blotting was used to detect protein expression levels and found that kaempferol could up-regulate the protein expressions of phosphorylated (p-) p65 and p65, and down-regulate the protein expression of sirtuin (SIRT) 1. Immunofluorescence was used to localize the expression of high mobility group box (HMGB) 1 and found its higher expression in outside of nucleus. However, the above effects of kaempferol on LIRI markedly attenuated by EX 527, a selective inhibitor of SIRT 1. Taken together, we first reported the protective effect of kaempferol on rat LIRI and confirmed that kaempferol's antiinflammation and antioxidative stress involving the SIRT1/HMGB1/NF-κB axis.